2019
DOI: 10.1088/1742-6596/1217/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

Contribution Indonesian Composite Index in PT Telekomunikasi Indonesia stock price model using 2-dimensional Geometric Brownian Motion

Abstract: Theoretically, the movement of the Composite Stock Price Index (CSPI) is in line with the company’s stock price movements. Hence, it would be appropriate to measure the CSPI contribution to the company’s stock price regarding modeling the company’s stock price. 2-dimensional Geometric Brownian Motion is believed to be the most appropriate model in this case. Therefore, this paper aims to project the share price of PT Telekomunikasi Indonesia in 2018 by considering the CSPI movement. The resulted mean absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, this trend cannot be made based on a definitive trend in the movement of share prices in the future because whatever predictions one might make can only be described as probabilistic and speculative (Chen et al 2018). Any sure prediction requires a standard order and an explainable pattern over a long period (Hoyyi et al 2019). If it is impossible to do this, the resultant implication is that the movement of share prices is only random (Liu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this trend cannot be made based on a definitive trend in the movement of share prices in the future because whatever predictions one might make can only be described as probabilistic and speculative (Chen et al 2018). Any sure prediction requires a standard order and an explainable pattern over a long period (Hoyyi et al 2019). If it is impossible to do this, the resultant implication is that the movement of share prices is only random (Liu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that the shorter the duration of the base period, the higher the prediction accuracy in the short term (Agustini et al 2018). For instance, researchers have found the prediction accuracy higher for one week's prediction (Hoyyi et al 2019), as shown by lower mean absolute percentage error (MAPE). Monte Carlo simulation considers the stock prices' randomness, drift, and volatility in its predictions (Lux 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They find the GBM approach to be “a safe model” for forecasts of daily closes for up to 2 weeks of investments. Hoyyi et al (2019) use a two‐dimensional GBM to model stock prices of PT Telekomunikasi Indonesia. Ladde and Wu (2009) and Wu (2010) use historical values and least squares regression to estimate drift and diffusion parameters for their modified GBM framework.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Traditionally, the drift and diffusion terms are estimated using historically returns and standard deviation (Benninga, 2014;Estember & Maraña, 2016;Sengupta, 2004;Urama & Ezepue, 2018), although some papers have attempted to use forecasted drift and diffusion terms (Abidin & Jaffar, 2014;Hoyyi et al, 2019;Ladde & Wu, 2009;Reddy & Clinton, 2016;Shafii et al, 2019;Surapaitoolkorn, 2009;Wu, 2010). Reddy and Clinton (2016) use expected drift estimated by using the capital asset pricing model (CAPM), but they nevertheless use historic diffusion term.…”
Section: Introductionmentioning
confidence: 99%
“…The former has its advantage of describing the decision-making for all points in the time horizon, while the later seeks one or limited several (multiple optimal stopping times) timings for some specific action and it handles both discrete and continuous environment. In the operation modelling of this paper, we mainly focus on the time to suspend or halt production under pressure of profitability and the decision is under consideration of time-continuous price dynamic, hence optimal stopping problem is established after modeling the price process with geometric Brownian motion, which is commonly used to simulate the variable on continuous time horizon, as applied in [10] for price forecasting, [11], [12] for stock trading, [13] for risk analysis and hedging.…”
Section: Introductionmentioning
confidence: 99%